2010
DOI: 10.17221/228/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of hydrolysis of egg white protein by pepsin

Abstract: results of nonlinear regression of the proposed kinetic model agreed with the experimental data, i.e. the average relative error was less than 5%. As a conclusion, the kinetic equations can be used to fit the enzymatic hydrolysis process of egg white protein and to optimise the operating parameters of bioactive peptides preparation for the bioreactor design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 27 publications
3
27
0
1
Order By: Relevance
“…It is suggested that high protein concentration became as a substrate in hibitor. The similar result was obtained by Ruan et al (2010) [16], it showed a decrease in DH at an increase in initial substrate concentration. According to Lescovac (2004) [17], the substrate concentration was the limiting factor.…”
Section: The Effect Of Initial Substrate Concentration On Degree Of Hsupporting
confidence: 86%
“…It is suggested that high protein concentration became as a substrate in hibitor. The similar result was obtained by Ruan et al (2010) [16], it showed a decrease in DH at an increase in initial substrate concentration. According to Lescovac (2004) [17], the substrate concentration was the limiting factor.…”
Section: The Effect Of Initial Substrate Concentration On Degree Of Hsupporting
confidence: 86%
“…A map dependent on the protein load complicates the comparison of deuteration levels for the protein in different states. This alteration suggests a level of substrate inhibition (21), and probably reflects a wide range of specificity constants (k cat /K m ) across the many individual cleavage sites presented in a protein substrate (22). Similar issues have been noted with trypsin (23).…”
mentioning
confidence: 53%
“…This equation modeled the degree of hydrolysis (h) as a function of the reaction time (t), which is the unique independent variable along with two kinetic constants (a, b) [12][13][14][15][16][17][18][19][20][21]. This model successfully described the typical shape of the protein hydrolysis time course and fit the experimental data with high accuracy, combining mechanistic foundation, simplicity and predictability.…”
Section: Introductionmentioning
confidence: 99%